Preliminary Evidence of Efficacy and Target Engagement of Pramipexole in Anhedonic Depression. Issue 2 (30th April 2022) - Ventorp, Filip; Lindahl, Jesper; van Westen, Danielle; Jensen, Jimmy; Björkstrand, Johannes; Lindqvist, Daniel
Abstract : Objective: To investigate feasibility and target engagement of high‐dose, add‐on pramipexole treatment in anhedonic depression. Method: In this open‐label pilot study, we included 12 patients with unipolar or bipolar, moderate‐to‐severe depression and with significant anhedonia symptoms. All patients were on a stable dose of one or a combination of antidepressants and/or mood stabilizers and received 10 weeks of adjunctive pramipexole titrated to a maximum dose of 4.5 mg salt/day. All patients were rated with the Dimensional Anhedonia Rating Scale (DARS), the Montgomery Åsberg Depression Rating (MADRS) and the Snaith Hamilton Pleasure Scale (SHAPS). Serum high‐sensitivity C‐reactive protein (hs‐CRP) was analyzed pre‐ and post‐treatment. Eight patients underwent fMRI pre‐ and post‐treatment and a simplified version of the monetary incentive delay task was used to investigate the effect of treatment on striatal activity during reward anticipation. Results: DARS, MADRS and SHAPS scores all improved significantly over 10 weeks of pramipexole treatment ( p <0.01). Mean levels of hs‐CRP decreased significantly over the course of treatment from mean 3.8 mg/L at baseline to 2.6 mg/L at endpoint ( p <0.01). There were significant treatment‐associated increases in reward related activity in several brain areas including the right lateral putamen, anterior left caudate, left posterior putamen, right dorsal caudate, left anterior putamen, and the right nucleus accumbens. Conclusions: This is the first study to suggest efficacy and target engagement of pramipexole in anhedonic depression. Larger randomized controlled trials are needed to confirm or refute these preliminary findings. Highlights: In this open‐label pilot study, high dose, add‐on pramipexole was a feasible and well‐tolerated treatment for anhedonic depression Serum high sensitivity C‐reactive protein decreased over the treatment course Add‐on pramipexole was associated with increased activity in the ventral striatum